A Phylogenetic Analysis of Chloroplast Genomes Elucidates the Relationships of the Six Economically Important Brassica Species Comprising the Triangle of U - Li, Peirong; Zhang, Shujiang; Li, Fei; Zhang, Shifan; Zhang, Hui; Wang, Xiaowu; Sun, Rifei; Bonnema, Guusje; Borm, Theo J. A. (Frontiers in Plant Science, 2017)
The Brassica genus comprises many economically important worldwide cultivated crops. The well-established model of the Brassica genus, U’s triangle, consists of three basic diploid plant species (Brassica rapa, Brassica oleracea and Brassica nigra) and three amphidiploid species (Brassica napus, Brassica juncea and Brassica carinata) that arose through interspecific hybridizations. Despite being extensively studied because of its commercial relevance, several aspects of the origin of the Brassica species and the relationships within and among these six species still remain open questions. Here, we successfully de novo assembled 60 complete chloroplast genomes of Brassica genotypes of all six species. A complete map of the Single Nucleotide Variants (SNVs) and Insertions and Deletions (InDels) in the chloroplast genomes of different Brassica species was produced. The chloroplast genome consists of a Large and a Small Single Copy (LSC and SSC) region between two Inverted Repeats (IRs), and while these regions of chloroplast genomes have very different molecular evolutionary rates, phylogenetic analyses of different regions yielded no contradicting topologies and separated the Brassica genus into four clades. B. carinata and B. juncea share their chloroplast genome with one of their hybridization donors B. nigra and B. rapa, respectively, which fits the U model. B. rapa, surprisingly, shows evidence of two types of chloroplast genomes, with one type specific to some Italian broccoletto accessions. B. napus clearly has evidence for two independent hybridization events, as it contains either B. rapa chloroplast genomes. The divergence estimation suggests that B. nigra and B. carinata diverged from the main Brassica clade 13.7 million years ago (Mya), while B. rapa and B. oleracea diverged at 2.18 Mya. The use of the complete chloroplast DNA sequence not only provides insights into comparative genome analysis but also paves the way for a better understanding of the phylogenetic relationships within the Brassica genus.